2005
DOI: 10.1074/jbc.m414656200
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Mutational Analysis of the SBDS Protein Family

Abstract: Shwachman-Diamond Syndrome (SDS) is an autosomal recessive disorder characterized by bone marrow failure with significant predisposition to the development of poor prognosis myelodysplasia and leukemia, exocrine pancreatic failure and metaphyseal chondrodysplasia. Although the SBDS gene mutated in this disorder is highly conserved in Archaea and all eukaryotes, the function is unknown. To interpret the molecular consequences of SDS-associated mutations, we have solved the crystal structure of the Archaeoglobus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(45 citation statements)
references
References 42 publications
1
41
0
Order By: Relevance
“…Recent studies on the SBDS orthologs suggested that SBDS is involved in RNA processing and ribosome biogenesis [12,13]. If these postulated functions of SBDS account for the accelerated apoptosis in SBDS-deficient cells, one would expect that inhibition of either RNA transcription or protein synthesis would results in marked cell death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies on the SBDS orthologs suggested that SBDS is involved in RNA processing and ribosome biogenesis [12,13]. If these postulated functions of SBDS account for the accelerated apoptosis in SBDS-deficient cells, one would expect that inhibition of either RNA transcription or protein synthesis would results in marked cell death.…”
Section: Discussionmentioning
confidence: 99%
“…The functions of the SBDS protein are unknown; however, various data suggest a role of SBDS in regulating apoptosis, [7,8] ribosomal biogenesis [9][10][11][12][13] and chemotaxis [14][15][16]. Since SDS marrows are hypocellular, [1,2,17] we previously asked whether SDS marrow progenitors undergo accelerated apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that SBDS is composed of three domains with weak contacts among them [8,9,10]. As SBDS family proteins share a similar structure and sequence, ScSBDS is expected to consist of domain I (Met1 -Gln94), domain II (Leu95 -Ala172), and domain III (Lys173 -Asn250) (Fig.…”
Section: Identification Of the Binding Region In Sbdsmentioning
confidence: 99%
“…S1), and missense mutations of SBDS associated with Shwachman-Diamond syndrome were identified in all three domains [8]. Nuclear magnetic resonance (NMR) spectroscopy identified domain I of SBDS as an RNA binding site [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation